Designing an English Learning Module for English for Tour Guide Course in English Language Education Program of STKIP Siliwangi Bandung - Ula Nisa El Fauzia, Intan Satriani, Gartika Pandu Bhuana, (LPPM Universitas Advent Indonesia, 2017)
English for Tour Guide is one of the courses in English Language Education Program of STKIP Siliwangi Bandung. This course uses “English for Professional Tour Guiding Services” as a textbook. Various problems are found when teachers use this book in the classroom. It predominantly deals with the materials. In response to this problem, this study aims to evaluate the use of “English for Professional Tour Guiding Services” book for students in English Language Education Program of STKIP Siliwangi Bandung. This research will apply quantitative and qualitative research design. There are two instruments in obtaining the data, namely questionnaire and interview. Through this study, it is expected that the strengths and weaknesses of this book can be found. Thus, suitable materials for the students can be designed. For the long term, it is expected that the result of this study can be used as a reference to make a book of English for Tour Guide course. Keywords: textbook evaluation, English for tour guide